Hydrological behaviour of vertisols in the Brazilian semi-arid region: the importance of rainfall of less than 30 mm - Andrade, Eunice; Rodrigues, Rafael; Palácio, Helba; Brasil, José; Guerreiro, Maria João (Revista Ciência Agronômica, 2020)
The greater probability of small rainfall events occurring in semi-arid regions, and the little understanding of their role in hydrological processes, has led to this investigation of surface runoff generated during these events in two adjacent micro basins in the Brazilian semi-arid region. The types of plant cover to be investigated were the Phytogeographical Caatinga Domain under regeneration for 35 years (CPDReg) and thinned CPD (CPDThin), which consisted of the elimination of trees with a diameter of <10 cm. Two historical series were considered, one of 40 years (1974-2013) with 2,259 events and the other consisting of 247 rainfall events of <30 mm from 2009 to 2013. The cumulative frequency distribution showed that the series of 247 24-hour events proved to be statistically representative in investigating hydrological processes in the Brazilian semi-arid region, compared to the long series of 2,259 events. Irrespective of the pattern, rainfall with an intensity of less than 17 mm h-1 generated effective precipitation with small depths (<2 mm). Regardless of the rainfall pattern, the lowest effective precipitation was registered for the plant cover of thinned CPD, both on an annual scale and per event. The occurrence of 3 or 4 consecutive dry days is enough for events of <30 mm to generate no runoff, due to the appearance of micro-cracks formed in vertisols during the drying process. It is believed, therefore, that the expansion and contraction of vertic soils is the main determinant for the start of Pe in areas with a water source (micro basins of <2 ha) in the CPD.